MUHAMMAD’S LIFE HISTORY: A GENEALOGICAL DISCOURSE THROUGH WESTERN 18 - 20 CENTURY VIEWS - Abdul Jabpar (LPPM STAI Muhammadiyah Probolinggo, 2019)
This paper describes the discourse of the image and biography of Prophet Muhammad in the view of Western scholars from the 18th century to the 20th century. Photographing the dynamics and development of their thinking in Critical Discourse Analysis (CDA) approach, through Foucault’s genealogy. The discourse focused on the features and characteristics of three important scholars of his time: Edward Gibbon, R. Bosworth Smith, and W. Montgomery Watt